1999
DOI: 10.1161/01.cir.100.19.1951
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Vasodilator Prostanoids and Nitric Oxide to Resting Flow, Metabolic Vasodilation, and Flow-Mediated Dilation in Human Coronary Circulation

Abstract: Background-Endothelial dysfunction is associated with atherosclerosis and may contribute to ischemic syndromes. We assessed the contribution of endothelium-derived nitric oxide (NO) and vasodilator prostanoids to resting blood flow, metabolic vasodilation, and flow reserve in the human coronary circulation. Methods and Results-Coronary hemodynamics were assessed before and after inhibition of vasodilator prostanoids and NO with intracoronary aspirin (acetylsalicylic acid [ASA]) and N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 50 publications
7
115
1
4
Order By: Relevance
“…Indeed, in general, endothelium-mediated (drug-and shear stress-stimulated) dilation of isolated coronary arteries is reduced in hypertensive humans 11,[53][54][55][56][57] and animals, 19,21,32,36,45,51,52,[58][59][60][61][62] while the endothelium-independent vasodilatory responses to sodium nitroprusside and adenosine are often unaltered. 21,32,45,55,63 There are exceptions to these general observations 18,33,50,[63][64][65][66] and the vessel type (conduit vs resistance artery), 45,57 the mode of precontraction, 33 and the vasodilator protocol 45,56,61,67 or eliminated 58,68,69 by inhibitors of eNOS in isolated coronary vessels from hypertensive animals, suggesting that NO remains an important component of vascular function even when its bioavailability is reduced in hypertension. In isolated pressurized coronary microvessels it was observed that removal of the endothelium increased the amount of myogenic constriction to a greater extent in SHR than in WKY over a wide pressure range.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 97%
“…Indeed, in general, endothelium-mediated (drug-and shear stress-stimulated) dilation of isolated coronary arteries is reduced in hypertensive humans 11,[53][54][55][56][57] and animals, 19,21,32,36,45,51,52,[58][59][60][61][62] while the endothelium-independent vasodilatory responses to sodium nitroprusside and adenosine are often unaltered. 21,32,45,55,63 There are exceptions to these general observations 18,33,50,[63][64][65][66] and the vessel type (conduit vs resistance artery), 45,57 the mode of precontraction, 33 and the vasodilator protocol 45,56,61,67 or eliminated 58,68,69 by inhibitors of eNOS in isolated coronary vessels from hypertensive animals, suggesting that NO remains an important component of vascular function even when its bioavailability is reduced in hypertension. In isolated pressurized coronary microvessels it was observed that removal of the endothelium increased the amount of myogenic constriction to a greater extent in SHR than in WKY over a wide pressure range.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 97%
“…Ruocco et al (26) demonstrated COX inhibition with indomethacin did not alter coronary blood flow in response to an experimentally induced flow-limiting coronary artery stenosis in pigs. However, COX inhibition in patients with coronary artery disease causes coronary vasoconstriction (8,11), thus suggesting that vasodilator PGs may play a greater role in the regulation of coronary vasomotor control in chronic vs. acute ischemia and in blood vessels subjected to atherosclerotic disease processes. By contrast, we recently demonstrated that adenosine receptor inhibition with aminophylline blunts the compensatory vasodilator response in the contracting human forearm subjected to acute hypoperfusion and is independent of NO (3).…”
Section: H266 Cyclooxygenase Inhibition and Skeletal Muscle Hypoperfumentioning
confidence: 99%
“…Wilson & Kapoor (1993) and Duffy et al (1998) previously detected that inhibition of cyclooxygenase with aspirin or indomethacin decreased the resting FBF by 20-30%. Prostacyclin also contributes to metabolic vasodilation (Kilbom & Wennmalm, 1976;Duffy et al, 1999a) as well as to resting and metabolic vasodilation in coronary arteries (Duffy et al, 1999b).…”
Section: Effect Of Antagonists On Baseline Vascular Tonementioning
confidence: 99%